1998
DOI: 10.1002/(sici)1099-0984(199805/06)12:3<151::aid-per296>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Self-knowledge and social desirability of personality traits

Abstract: Research into the self‐concept has shown that self‐knowledge is affected by factors such as trait desirability, trait vagueness, and self‐variability. Among these, social desirability appears to play a prominent role. In a multidimensional view of the self, however, several studies indicate that in special conditions people show adequate self‐knowledge in specific personality dimensions. The present study tests this with respect to extraversion and anxiety predisposition on a sample of 160 late adolescents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The present research has a few limitations: our exploratory study, based on a self-administered web survey, restricted the participation to the survey only to a convenience sample of people equipped with an Internet connection (Couper, 2000). Furthermore, self-report questionnaires evaluate subjective characteristics and, as is well known, can be biased from social desirability and acquiescence (Meleddu and Guicciardi, 1998). However, the anonymity and the short duration of the survey may have limited these biases.…”
Section: Discussionmentioning
confidence: 99%
“…The present research has a few limitations: our exploratory study, based on a self-administered web survey, restricted the participation to the survey only to a convenience sample of people equipped with an Internet connection (Couper, 2000). Furthermore, self-report questionnaires evaluate subjective characteristics and, as is well known, can be biased from social desirability and acquiescence (Meleddu and Guicciardi, 1998). However, the anonymity and the short duration of the survey may have limited these biases.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, a sample of respondents evaluate how desirable they personally regard a particular characteristic, and aggregated scores of these judgments are assumed to represent the incentives for SD-bias (Meleddu & Guicciardi, 1998). This is a valid indicator when (a) the underlying personal preferences represent the normative climate in the surveyed population and when (b) the sample of informants is representative for those respondents for which the aim is to predict SD-bias.…”
Section: Measures Of Desirability Beliefs and Their Underlying Assumpmentioning
confidence: 99%
“…In their study of student leaders at the US Naval Academy, Roush and Atwater (1992) also found individuals high on introversion provided performance ratings better aligned with those provided by their subordinates. Meleddu and Guicciardi (1998) found extraverted individuals tend to provide more socially desirable ratings. In the context of 360 performance evaluation, an extraverted individual may be inclined to provide high self-ratings of performance as these may be seen as more socially desirable than lower ratings.…”
Section: Personality Characteristics Potentially Associated With Selfmentioning
confidence: 99%